Exercise Training and Neurodegeneration in Mitochondrial Disorders: Insights From the Harlequin Mouse - Fernández-de la Torre, Miguel; Fiuza-Luces, Carmen; Valenzuela, Pedro L.; Laine-Menéndez, Sara; Arenas, Joaquín; Martín, Miguel A.; Turnbull, Doug M.; Lucia, Alejandro; Morán, María (Frontiers in Physiology, 2020)
Aim: Cerebellar neurodegeneration is a main phenotypic manifestation of mitochondrial disorders caused by apoptosis-inducing factor (AIF) deficiency. We assessed the effects of an exercise training intervention at the cerebellum and brain level in a mouse model (Harlequin, Hq) of AIF deficiency. Methods: Male wild-type (WT) and Hq mice were assigned to an exercise (Ex) or control (sedentary [Sed]) group (n=10–12/group). The intervention (aerobic and resistance exercises) was initiated upon the first symptoms of ataxia in Hq mice ( 3 months on average) and lasted 8 weeks. Histological and biochemical analyses of the cerebellum were performed at the end of the training program to assess indicators of mitochondrial deficiency, neuronal death, oxidative stress and neuroinflammation. In brain homogenates analysis of enzyme activities and levels of the oxidative phosphorylation system, oxidative stress and neuroinflammation were performed. Results: The mean age of the mice at the end of the intervention period did not differ between groups: 5.2±0.2 (WT-Sed), 5.2±0.1 (WT-Ex), 5.3±0.1 (Hq-Sed), and 5.3±0.1 months (Hq-Ex) (p=0.489). A significant group effect was found for most variables indicating cerebellar dysfunction in Hq mice compared with WT mice irrespective of training status. However, exercise intervention did not counteract the negative effects of the disease at the cerebellum level (i.e., no differences for Hq-Ex vs. Hq-Sed). On the contrary, in brain, the activity of complex V was higher in both Hq mice groups in comparison with WT animals (p< 0.001), and post hoc analysis also revealed differences between sedentary and trained Hq mice. Conclusions: A combined training program initiated when neurological symptoms and neuron death are already apparent is unlikely to promote neuroprotection in the cerebellum of Hq model of MD, but it induces higher complex V activity in the brain.